Emotional proprioception: Treatment of depression with afferent facial feedback. (September 2016) - Finzi, Eric; Rosenthal, Norman E.
Abstract: We develop the concept of emotional proprioception, whereby the muscles of facial expression play a central role in encoding and transmitting information to the brain's emotional circuitry, and describe its underlying neuroanatomy. We explore the role of facial expression in both reflecting and influencing depressed mood. The circuitry involved in this latter effect is a logical target for treatment with botulinum toxin, and we review the evidence in support of this strategy. Clinical trial data suggest that botulinum toxin is effective in treating depression. We discuss the clinical and theoretical implications of these data. This novel treatment approach is just one example of the potential importance of the cranial nerves in the treatment of depression.